Perbedaan Tingkat Ketergantungan Nikotin Berdasarkan Uji Hooked On Nicotine Checklist (HONC) Antara Kelompok Perokok Hipertensi dan Non-Hipertensi di Poliklinik Dalam RSUD Singaparna Medika Citrautama - Hilal Muhammad Dimas Nugraha (UNISBA Press, 2022)
Abstract. Cigarettes can cause several side effects for the body. Smoking is still the cause of death of more than 7 million cases per year. A person who smokes cigarettes containing more than one pack of nicotine per day will trigger the disease, namely hypertension which is dangerous to the body. This study aims to determine differences in nicotine dependence levels based on the Hooked On Nictotine Checklist (HONC) test in hypertensive and non-hypertensive smokers at Singaparna Medika Citrautama Hospital, conducted in March - November 2021. This type of qualitative research uses comparative analysis method with a case control approach. Data were obtained from the results of distributing the HONC questionnaire to hypertensive and non-hypertensive patients at the Inner Polyclinic of Singaparna Medika Citrautama Hospital. Data analysis used independent t test and Mann Whitney. The number of samples is 72 people. Data processing using SPSS 25.00 for Mac statistical application. The results of the study showed that 28 patients with nicotine dependence (77.78%) and non-hypertensive patients (27.22%) were dependent on nicotine and 26 people (72.22%) were not dependent on nicotine (27). ,28%). The difference in the level of dependence p-value 0.009 (<0.05) means that there is a difference in the level of nicotine dependence between the hypertensive group and non-hypertensive smokers. In conclusion, there is a significant difference in the level of nicotine dependence of hypertensive and non-hypertensive patients at Singaparna Medika Citrautama Hospital. Abstrak. Rokok dapat menyebabkan beberapa efek samping bagi tubuh. Merokok masih menjadi penyebab kematian lebih dari 7 juta kasus pertahun. Seorang menghisap rokok mengandung nikotin lebih dari satu bungkus perhari maka akan memicu penyakit yaitu hipertensi yang membahayakan tubuh. Penelitian ini bertujuan mengetahui perbedaan tingkat ketergantungan nikotin berdasar atas uji Hooked On Nictotine Checklist (HONC) pada perokok Hipertensi dan Non Hipertensi di RSUD Singaparna Medika Citrautama dilakukan Maret - November 2021. Jenis penelitian kualitatif dengan metode comparative analisis dengan pendekatan cases control. Data diperoleh dari hasil penyebaran kuesioner HONC kepada pasien hipertensi dan non-hipertensi di Poliklinik Dalam RSUD Singaparna Medika Citrautama. Analisis data menggunakan uji t independent dan mann whitney. Jumlah sampel 72 orang. Pengolahan data menggunakan aplikasi statistika SPSS 25.00 for Mac. Hasil penelitian, pasien hipertensi dengan ketergantungan nikotin sebanyak 28 orang (77,78%) dan tidak ketergantungan 8 orang (27,22%) pasien non-hipertensi ketergantungan nikotin 26 orang (72,22%) dan tidak ketergantungan sebanyak 20 orang (27,28%). Perbedaan tingkat ketergantungan p-value 0,009 (<0,05) artinya terdapat perbedaan tingkat ketergantungan nikotin antara kelompok hipertensi dan perokok non hipertensi. Kesimpulan, terdapat perbedaan bermakna tingkat ketergantungan nikotin pasien hipertensi dan non-hipertensi di RSUD Singaparna Medika Citrautama.